Socio-Personal Factors Influencing Job Commitment and Social Commitment among the Veterinarians in Kerala - Soumya Sankar; Reeja George.P and P. J. Rajkamal (Asian Journal of Research in Business Economics and Management, 2014)
The study was conducted among the veterinarians of the Department of Animal Husbandry, Kerala. Questionnaire method of data collection was adopted. Total of 200 veterinarians were selected for the study Result revealed that majority of the respondents in the sample belonged to the age group of 31-40 years and were males. Majority of the respondents were working within 50 kilometers of their homes and had 8 to 16 years of work experience. In the case of 64 per cent of the respondents the age of the youngest child was three years and had three to four dependants in their family. Out of the six socio- personal variables studied, age and experience were significantly and positively correlated with social commitment and none of the variable has influence on job commitment.